A Network Meta-analysis of Primary Hypertension Management Patterns in China - GU Mingyu, QIN Tingting, QIAO Kun, BAI Xinyuan, WANG Yao, YANG Yutong, LI Xingming (Zhongguo quanke yixue)
Background Hypertension as a risk factor can significantly increase the morbidity and mortality of cardiovascular and cerebrovascular diseases, and effective control of hypertension is the key to prevent and treat cardiovascular diseases. Objective Collect literature on the evaluation of the effectiveness of hypertension management models in China. Evaluate the management effects of different models and provide a reference for further optimization of hypertension management models. Methods Using StataSE-64, a network Meta-analysis of the 18 included hypertension management model papers was performed using blood pressure control rates as an evaluation metric. The models included five models: joint hospital-community management, community management, hospital treatment management, general management, and combined Internet management. Results Joint hospital-community management, community management, hospital management, and combined Internet management are all effective for hypertension control. The order is joint hospital-community management ≈ combined Internet management> hospital treatment management>community management>blank control. Among them, the joint hospital-community management model has significant effect on hypertension control; the joint hospital-community management model and combined Internet management has similar effect; and hospital management has better effect than community management. Conclusion In order to improve the hypertension management model, the construction of hospital-community-family management model in primary health care institutions should be promoted, and the combination of chronic disease management model and combined Internet model should be guided to strengthen the whole-life, whole-cycle management of chronic disease patients.